2023
DOI: 10.1101/2023.05.02.538995
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A global catalog of whole-genome diversity from 233 primate species

Abstract: The rich diversity of morphology and behavior displayed across primate species provides an informative context in which to study the impact of genomic diversity on fundamental biological processes. Analysis of that diversity provides insight into long-standing questions in evolutionary and conservation biology, and is urgent given severe threats these species are facing. Here, we present high coverage whole-genome data from 233 primate species representing 86% of genera and all 16 families. This dataset was us… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 174 publications
0
4
0
Order By: Relevance
“…The successful identification of informative markers, even when using evolutionary distant reference Y chromosome sequences, suggests that this approach could be applied more extensively. This is particularly of relevance considering that a total of 30 Y chromosome references and WGS from 86% of primate genera became available following recent publications 39 , 42 . Targeting species in key primate groups to assemble Y chromosome references would make possible a more extensive application of the approach presented here.…”
Section: Discussionmentioning
confidence: 99%
“…The successful identification of informative markers, even when using evolutionary distant reference Y chromosome sequences, suggests that this approach could be applied more extensively. This is particularly of relevance considering that a total of 30 Y chromosome references and WGS from 86% of primate genera became available following recent publications 39 , 42 . Targeting species in key primate groups to assemble Y chromosome references would make possible a more extensive application of the approach presented here.…”
Section: Discussionmentioning
confidence: 99%
“…These shifts were responsible for the limited geographic distribution of the populations, et al, 2019) led to episodes of population contractions in the last 70 Kya, as we found in our demographic analysis (Table 1). These events also explain the relatively low genetic diversity found in Cacajao (Kuderna et al, 2023).…”
Section: The Evolutionary History Of Cacajaomentioning
confidence: 95%
“…The demographic parameters of the best-fit model, as well as the confidence intervals, were calculated from 100 parametric bootstrap replications, using jSFS obtained from the simulation run with the best composite likelihood value. For time estimates, we applied a mutation rate of 8.48 x 10 -9 substitutions per site per generation (Kuderna et al, 2023).…”
Section: Demographic Analysesmentioning
confidence: 99%
“…Despite the long SLC22A10 isoform not being annotated in RefSeq for bonobo and orangutan, we included these two species in the alignment considering the plausibility of the protein model in the context of their genomes and the high genomic conservation in comparison to chimpanzee and gorilla. Allele frequencies from non-human great apes were obtained from available whole-genome sequencing data including 59 chimpanzees, 10 bonobos, 49 gorillas and 16 orangutans [48][49][50][51] . All samples were mapped to Hg19.…”
Section: Sequencing Data Processing and Analyses Of Slc22a10 In Great...mentioning
confidence: 99%